THE NUMBER of (Aedes sp.) EGGS LAYING ON DIFFERENCES TYPE AND SPECIES OF PHYTOTELMATA IN AREA OF LAMPUNG UNIVERSITY - Saskya Ramadhanti; EMANTIS ROSA; Elly Lestari Rustiati; Tugiyono Tugiyono (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2020)
Phytotelmata is the part of a plant that can collect water and can be used as a natural breeding site for insects including mosquitoes. This research was conducted in August-December 2019 in the University of Lampung to find out the number of egg in phytotelmata and find the type and species of phytotelmata which are natural breeding site for Aedes sp. This study used an observatory method with a descriptive approach in the field. Analysis data was done using ANOVA and continued with the BNT test with 95% (a=5%) confidence. This research show that it found 3 types of phytotelmata like fruit hole, tree hole, axillary with six species of Phytotelmata such as Cocos nucifera, Artocarpus heterophyllus, Bambusa sp., Bauhinia purpurea, Colocasia esculenta, and Musa paradisiaca. The most potential species of phytotelmata became the natural breeding site for Aedes sp. mosquito is a Cocos nucifera with an average of 16,33 eggs.